Biomass derived carbon aerogel as an ultrastable skeleton of form-stable phase change materials for efficient thermal energy storage - Zou, Zhiqiang; Wu, Wei; Wang, Yi; Drummer, Dietmar (Materials Research Express, 2020)
Direct conversion of biomass to carbon aerogel provides a promising approach to developing supporting material for phase change materials (PCMs). In present work, carrot and pumpkin derived carbon aerogels (CCA and PCA) were fabricated via a hydrothermal and post-sintering process. N-2 adsorption-desorption isotherms were used to evaluate the specific surface area and pore distribution of the carbon aerogels. It showed that the carrot carbon aerogel sintered at 800 degrees C (CCA800) possessed a specific surface area of 33.80 m(2)g(-1), which is separately 168%, 165%, and 287% higher than that of carrot carbon aerogel sintered at 1000 degrees C (CCA1000, 12.59 m(2)g(-1)), pumpkin carbon aerogel sintered at 800 degrees C (PCA800, 12.77 m(2)g(-1)), and pumpkin carbon aerogel sintered at 1000 degrees C (PCA1000, 8.74 m(2)g(-1)). Owing to its porosity, the carbon aerogels with a high loading content of palmitic acid (PA)/thiol-ene resin (TE) composite as a PCM without leakage. A thermal conductivity enhancement of 60.5% was achieved by 50PA/TE@PCA1000 compared with 50PA/TE, and DSC result showed its latent heat of 88.26 J/g. The excellent properties of PCMs composites lead to a promising application foreground.
CRIS-Team WoS Importer:2020-05-12